Factors affecting complementary feeding among mothers of under two years children in Darai and Kumal communities of Mangalpur, Chitwan - Kandel, K P; Sah, B K; Kafle, S; Khanal, S; Adhikari, B (Journal of Chitwan Medical College, 2017)
Complementary feeding for an infant refers to timely introduction of safe and nutritional foods in addition to breast-feeding i.e. clean and nutritionally rich additional foods introduced at about six months of infant age. Complementary feeding strategies encompass a wide variety of interventions designed to improve not only the quality and quantity of these foods but also improve the feeding behaviors. The objective of the study is to assess the factors affecting complementary feeding practices among mothers in Mangalpur, Chitwan. A cross sectional study was carried out to find out the factors affecting complimentary feeding practices among mothers of under two years children in Darai and Kumal Communities in Mangalpur, Chitwan. Altogether 84 respondents were included in this study. Data analysis was done by descriptive statistics and Inferential statistics and those data was analyzed by using the software SPSS (version 20.0). The percentage of Knowledge on complimentary feeding was found as 96.40 and correct practice was 73.80% in the study area. In this study, more than half (58.3%) of the respondent had first child at the age of nineteen or more. 86.90 % of the respondents had knowledge of complementary food and mostly (87.70) practiced lito as complimentary food. Almost all (98.80%) mothers had the knowledge of sarbottam pitho and 79.50% had correct knowledge of preparation. Complementary feeding was practiced correctly by 73.80% mothers